Teaching Material and Method toward English Students at Vocational High School - Raudhatul Islam (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This research aimed to analyze the English learning method toward students at SMK Hafsawaty Zainul Genggong Probolinggo and found out which material are relevant to their needs. This research used a qualitative research involving twenty students and English teachers at SMK Hafsawaty Zainul Hasan Genggong. Data obtained by using interviews, questionnaires, documentation, then analyzed using qualitative data analysis method. The interview was purposed for an English teacher and the questionnaire was filled by twenty students. The result of this research found that the students could be easy to understand the material that deliver by the teacher. It proved that the teaching method applied by the teacher was appropriate for the students need. From the teaching material, the school had to develop the education system by considering the teaching material needs for the vocational students. Then, when viewed from the needs, the material has not focused on the needs of students majoring in Islamic banking. However, English for specific purposes have to consider the material need for the students.